Women’s learning motivations: Qualitative inquiry of doctoral students in civil engineering - Dos Santos, Luis Miguel (Frontiers in Education, 2022)
Professional practice and engineering education are important developments in the field of engineering. Based on Social Cognitive Career and Motivation Theory, this study aims to understand the motivations, reasons, and career decisions of doctoral students of civil engineering. Specifically, the researcher aims to understand the motivations and reasons that may influence students’ decision-making processes, particularly those of women, in regard to joining a doctoral degree programme in engineering. An interpretative phenomenological analysis was utilised in this study, with three interview sessions and one focus group activity employed for data collection. The findings indicate that achievements regarding education and career goals (becoming leading engineers and engineering educators), interests in career development (achieving advanced qualifications to obtain higher leadership positions), and the importance of surrounding environments and individuals (integral to One Belt One Road opportunities) are the main motivations and sense-making elements in regard to career decisions. Government leaders, human resources planners, department heads, university leaders, organisational managers, and other researchers may use this study as a blueprint to reform and improve their human resources management and engineering education schemes based on the recommendations and desires of scientists.